Non-steroidal Anti-inflammatory Drugs Are Unlikely to Inhibit Radiographic Progression of Ankylosing Spondylitis: A Systematic Review - Zhang, Jing-Ru; Pang, Dan-Dan; Dai, Sheng-Ming (Frontiers in Medicine, 2019)
Objective: To clarify if non-steroidal anti-inflammatory drugs (NSAIDs) could retard the disease progression of ankylosing spondylitis (AS). Methods: A systematic search of Embase, Pubmed and the Cochrane Central Register of Controlled Trials (CCRCT) databases was conducted. Structural damage of AS was evaluated using spinal radiographs to assess modified Stoke Ankylosing Spondylitis Spine Score (mSASSS). Results: Five full-text papers (from 2 prospective and 2 retrospective studies) were included. Of the 4 studies deemed relevant, 3 reported no significant inhibition of spinal progression in AS patients treated continuously with NSAIDs, as determined by radiograph over 2-3 years. Only the 1st prospective randomized trial demonstrated that 2-year continuous use of celecoxib reduced mean changes in mSASSS of AS patients compared with on-demand treatment. However, the dosage difference of celecoxib between the two groups in the study seemed to be too small to elicit such differences in radiographic progression, while the therapy did not elicit any differences in disease activity, C-reactive protein (CRP) levels or global pain. Of the 3 studies that reported radiographic progression in the subgroup with elevated CRP, only post-hoc analysis of the 1st randomized study revealed that the patients treated continuously with NSAIDs had less radiological progression than those using on-demand NSAIDs. In 2 studies that reported radiographic progression in the patient subgroup with baseline syndesmophytes, both reported that there was no significant inhibition of progression of mSASSS in patients who had received continuous NSAID treatment compared with patients given on-demand NSAIDs. Conclusion: The available evidence suggests that NSAIDs are unable to delay radiographic progression of AS even in patients with elevated CRP levels.